"Jumping the Shark": An Interdisciplinary Activity for Engaging Students With the Principles of Bivariate Regression. (October 2022) - Watson, Todd D.
Background: Student anxiety about statistics may lead to poorer learning outcomes. Objective: The purpose of this study was to evaluate an exercise designed to teach students in an introductory statistics class the principles of bivariate regression and to emphasize how statistical tools used by psychologists are also implemented in other fields. Method: Students used a published model on the relationship between tooth size and the length of great white sharks to estimate the length of extinct sharks and to explore factors that could affect the accuracy or validity of regression analyses. Data from an anonymous self-report scale were used to assess the activity. Results: More than 95% of respondents agreed or strongly agreed that the activity was engaging, approximately 95% of students agreed or strongly agreed that the activity helped them learn about factors that can lead to problems with bivariate correlation/regression, and approximately 91% of respondents correctly answered a question designed to assess basic content acquisition. Conclusion: Feedback data suggest that the exercise was successful in achieving its content and process learning goals. Teaching Implications: Implementation of similar exercises may improve student engagement and outcomes in psychology statistics courses.